Kollaboratív problémamegoldó képességet vizsgáló dinamikus teszt fejlesztése - Pásztor-Kovács, Anita; Pásztor, Attila; Molnár, Gyöngyvér (Magyar Pedagógia, 2018)
The ability to effectively solve problems in collaboration with others represents an increasingly important asset in the modern workforce. Thus, there is an urgent necessity to develop collaborative problem-solving (ColPS) skills in an educational context. Reaching this aim requires effective developmental programs and effective instruments, which are suitable for large-scale measurements and everyday school practice. The purpose of the present research is to develop an online interactive instrument for assessing ColPS and to investigate its applicability in two small-scale studies. We transformed the individual interactive problem-solving tasks on the eDia platform based on the MicroDYN approach into collaborative ones by making them interdependent. Our aim was to create a testing environment which could provide the future option of automatic coding and computer agent embedding. We implemented predefined messages and several further innovative ways to communicate: students were able to exchange visual information, for example. The results from our studies showed that the seventh- and eighth-grade students in our samples were generally able to use these new communication options. Even in the second study, when we completely eliminated free chat, students managed to solve the problems using restricted communication. However, this condition posed a major challenge for many of them. Students provided valuable input to improve our instrument, for instance, in terms of increasing the predefined message set based on their interactions and opinions about the test. This study has contributed to a deeper analysis of the ColPS construct and taken the first steps toward creating an effective and potentially valid ColPS instrument.